2018
DOI: 10.1101/352088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pyriproxyfen metabolite 4'OH- pyriproxyfen disrupts thyroid hormone signaling and enhances Musashi-1 levels in neuroprogenitors.

Abstract: 12Epidemiological and experimental studies have raised questions as to whether the insecticide 13 pyriproxyfen (PPF) could be implicated in the increased incidence of microcephaly associated 14 with ZIKA infection during pregnancy. This pesticide is documented as a thyroid hormone (TH) 15 disrupting chemical. We investigated whether environmentally relevant amounts of its main 16 metabolite, 4'-OH-pyriproxyfen (4'-OH-PPF), modified TH signaling and early neuronal 17 development. First, an in silico study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Despite its broad use, pyriproxyfen has been shown to affect the central nervous system. The main pyriproxyfen metabolite, 4'OH-pyriproxyfen, alters gene expression in mouse neurospheres cultures, indicating possible consequences on neurogenesis and brain morphology (Spirhanzlova et al, 2018). Moreover, rat pups chronically exposed to pyriproxyfen showed arhinencephaly and reduced brain weight (Evans et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its broad use, pyriproxyfen has been shown to affect the central nervous system. The main pyriproxyfen metabolite, 4'OH-pyriproxyfen, alters gene expression in mouse neurospheres cultures, indicating possible consequences on neurogenesis and brain morphology (Spirhanzlova et al, 2018). Moreover, rat pups chronically exposed to pyriproxyfen showed arhinencephaly and reduced brain weight (Evans et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that amphibian tadpoles are the most famous developmental stage for ecotoxicological contaminants among terrestrial amphibian adults (Yan et al, 2012). However, PPF is recognized as an interfering agent with thyroid hormones essential for amphibians' development and signaling (Spirhanzlova et al, 2018;Wegner and Stolt, 2005). Additionally, Ose et al, (2017) reported that there were no observed mortality rate and other adverse symptoms through recorded daily actions through the Nieuwkoop and Faber stage 51 of African clawed frog, Xenopus laevis, exposed to pure PPF.…”
Section: Pyriproxyfen Effects On Amphibiamentioning
confidence: 99%
“…Additionally, Ose et al, (2017) reported that there were no observed mortality rate and other adverse symptoms through recorded daily actions through the Nieuwkoop and Faber stage 51 of African clawed frog, Xenopus laevis, exposed to pure PPF. Spirhanzlova et al, (2018) claimed that low affinity binding activities of PPF to TRα1 on transgenic Tg (thibz:GFP) X. laevis tadpoles triggering the impacts of ecologically relevant concentrations of PPF and its primary metabolite (4′-OH-Pyr) on thyroid hormone signaling and early brain development exhibited their abnormalities. Lajmanovich et al, (2019) investigated the impacts on enzymatic activities, hormone levels, and behavioral activity of PPF on premetamorphic tadpoles, after their exposure to 0.1 mg PPF/L and 0.01 mg/L of PPF for 22 days.…”
Section: Pyriproxyfen Effects On Amphibiamentioning
confidence: 99%